United we serve : national service and the future of citizenship - Dionne, E. J., Jr; Drogosz, Kayla Meltzer; Litan, Robert E., 1950- (Brookings Institution Press, 2003)
Annotation Public rhetoric in the United States has always laid heavy stress on the obligations of citizenship. Bill Clinton praised the idea of service, and so does George W. Bush. Since September 11, the debate over service and the obligations of citizenship has become even more urgent. United We Serve gathers many diverse voices on civic life and civic obligation to explore the idea of national service as it relates to citizenship. Activists and practitioners discuss the rise of the service movement, its practical successes, and its challenges. Policymakers and political leaders explore the links between service and problem solving. Political scientists and philosophers connect the service debate to larger concerns about democratic participation. The book also includes a lively debate over whether the U.S. should reconsider compulsory national service. The discussion about service is a debate over how Americans think of themselves and their nation -- and about what the "new patriotism" means. Contributors include: Daniel Blumenthal, Harry Boyte, John M. Bridgeland, Louis Caldera, Bruce Chapman, former President Bill Clinton, Charles Cobb Jr., Jane Eisner, Jean Bethke Elshtain, William Galston, Stephen Goldsmith, Robert D. Haas, Stephen Hess, Peter D. Hart and Mario A. Brossard, Alan Khazei, John Lehman, Leslie Lenkowsky, Paul C. Light, Michael Lind, Tod Lindberg, Will Marshall and Marc Magee, Senator John McCain, Charles Moskos, Robert Putnam, Representative Charles Rangel, Alice M. Rivlin, Michael Schudson, Mark Shields, Carmen Sirianni, Theda Skocpol, Andrew L. Stern, Jeff Swartz, Steven Waldman, Caspar Weinberger, David Winston, Harris Wofford, and Robert Wuthnow